THE INFLUENCE OF ANXIETY LEVEL AND PAST COVID-19 ON SLEEP QUALITY AND INSOMNIA SEVERITY - Boiko, D.I.; Zhyvotovska, A.I.; Skrypnikov, A.M. (World of Medicine and Biology, 2022)
Based on recent studies, we put forward a hypothesis about the synergistic effect of anxiety disorders and previous COVID-19 on the deterioration of the quality of sleep and occurring of insomnia. The purpose of the study was to investigate the impacts of anxiety disorders, and COVID-19 on anamnesis and its combined effect on sleep disturbances. We conducted a case-control study, which included 60 patients, who were divided into 3 groups depending on the occurrence of anxiety disorders and COVID-19 in their medical history during the last 6 months. Patients were assessed by the Beck anxiety inventory, Pittsburgh Sleep Quality Index, and the Insomnia Severity Index. We found a worsening sleep quality and a higher frequency of insomnia in patients with COVID-19. Along with this, concomitant anxiety disorders worsened both the quality of sleep and the level of insomnia in these respondents. It was determined that patients with an anxiety disorder with a history had a lower subjective assessment of sleep quality, higher sleep latency, and more pronounced diurnal dysfunction, while patients without a history had better sleep efficiency and a lower frequency of sleeping pills. Anxiety disorders and having experienced COVID-19 are associated with poorer sleep quality and more severe insomnia. Their combination significantly reduces the quality of sleep and increases the degree of insomnia. These findings suggest a potential role for COVID-19 in exacerbating the association between anxiety and sleep disorders.